Mengoptimalkan kualitas pendidikan Madrasah Tsanawiyah: Strategi dan implikasinya bagi prestasi siswa - Rusyda, Layyin Aro Aufa (Maliki Interdisciplinary Journal, 2024)
This study aims to examine effective strategies for improving the quality of Madrasah Tsanawiyah through appropriate approaches, optimal implementation, and their impact on student achievement. Improving the quality of education is a crucial issue for Madrasah Tsanawiyah as an Islamic educational institution that has a strategic role in educating the nation. However, various problems such as limited resources and suboptimal management still hinder efforts to improve the quality of madrasah. The method used in this research is a literature study by analyzing various relevant sources such as scientific articles, books, and research reports. The results of the study indicate that there are three effective strategies that can be applied to improve the quality of Madrasah Tsanawiyah, namely: 1) the application of a total quality management approach that emphasizes continuous improvement by involving all components of the madrasah; 2) the implementation of an innovative curriculum that is relevant to the needs of students, integrating religious and general sciences, and developing 21st-century skills; and 3) optimizing the leadership role of madrasah principals who are visionary, transformative, and able to build a quality culture within the madrasah environment. The application of these strategies has been proven to have a positive impact on improving students' academic and non-academic achievement. However, the successful implementation of strategies to improve the quality of madrasah requires support and cooperation from all stakeholders as well as synergistic and continuous efforts.